2017
DOI: 10.1088/2053-1583/aa75ed
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of magnetic anisotropy in two dimensional CrI3

Abstract: Abstract.The observation of ferromagnetic order in a monolayer of CrI 3 has been recently reported, with a Curie temperature of 45 Kelvin and off-plane easy axis. Here we study the origin of magnetic anisotropy, a necessary ingredient to have magnetic order in two dimensions, combining two levels of modeling, density functional calculations and spin model Hamiltonians. We find two different contributions to the magnetic anisotropy of the material, favoring off-plane magnetization and opening a gap in the spin … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

57
663
6
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 687 publications
(728 citation statements)
references
References 59 publications
57
663
6
2
Order By: Relevance
“…However, this effect is expected to be weak in trivalent chromium with electronic configuration 3d 3 and nearly octahedral coordination due to quenching of the orbital moment. Thus single ion anisotropy should be weak for Cr, as was demonstrated recently for CrI 3 by Lado and Fernández-Rossier [28]. In that study, spin-orbit coupling on the heavy iodine ions was found to contribute the majority of the anisotropy through Cr-I-Cr superexchange.…”
Section: B Magnetic Behavior and Phase Transitionssupporting
confidence: 70%
See 2 more Smart Citations
“…However, this effect is expected to be weak in trivalent chromium with electronic configuration 3d 3 and nearly octahedral coordination due to quenching of the orbital moment. Thus single ion anisotropy should be weak for Cr, as was demonstrated recently for CrI 3 by Lado and Fernández-Rossier [28]. In that study, spin-orbit coupling on the heavy iodine ions was found to contribute the majority of the anisotropy through Cr-I-Cr superexchange.…”
Section: B Magnetic Behavior and Phase Transitionssupporting
confidence: 70%
“…Since the Cr-Cr distances increase with increasing halogen size, the direct exchange is expected to be weakened along this series. This indicates that superexchange, which is expected to favor ferromagnetic alignment, is the more important magnetic interaction [28]. As the electronegativity is decreased from Cl to Br to I, it is expected that the Cr-halogen bonding becomes more covalent, strengthening superexchange interactions and raising ordering temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed understanding of the low-temperature magnetic behavior of the W@InI 3 monolayer would be useful for further analyses. We therefore use the quantum mechanical treatment, i.e., the linear spin wave approximation, to study the magnon excitation of this system [40]. This could also allow us to study the spin wave related thermal and topological properties [41][42][43].…”
Section: B Magnetic Configuration and Magnetic Behavior Under Finitementioning
confidence: 99%
“…Since the integral is controlled by E − (k), its value is dominated by the integral near the point. Thus, following the spirit of the Debye model, we assume that the integral is within a circular region (within a cutoff radius k c ), which provides good approximation of the main behavior [40]. In order to obtain T c , we need to address when M decreases to an obvious small value.…”
Section: B Magnetic Configuration and Magnetic Behavior Under Finitementioning
confidence: 99%